The Ancient Era and the Problem of the 'Break of Epochs' in Viktor Petrov's Vision: the Discreteness of the Ukrainian Historical Process - Andryeyev, Vitaliy; Lukashenko, Alisa (Skhid, 2025)
The article is devoted to the study of the Theory of Epochs developed by the prominent Ukrainian thinker and scholar Viktor Petrov (V. Domontovych) and its verification based on the materials of ancient Ukrainian history, particularly the archaeological cultures of the Black Sea region and the Dnipro basin. Petrov’s theory offers a fundamentally different view of historical development, rejecting its linearity and evolutionism. Instead, it defines the historical process as discrete, emphasizing the isolation and self-sufficiency of individual epochs in the formation of the Ukrainian people. In this context, an epoch is understood as a structural, internally closed entity determined by a dominant ideology, a stable economic foundation, and established social institutions. Rather than continuing one another, epochs replace or oppose each other, thus forming the overall historical process through “breaks” – ruptures and crises. The Ancient Era represents one such crucial stage in Slavic and Ukrainian ethnogenesis (Ith century BCE – IV th century CE). The article examines the chronological boundaries and conceptual content of this period, which Petrov viewed as a “barbarian variant” of the Hellenistic civilization north of the Black Sea. In particular, the study defines the role of Roman influence, which, according to Petrov, was not decisive but merely contributed to individual Romanization. Meanwhile, the Zarubyntsi and Chernyakhiv cultures are interpreted as examples of local modifications of self-sufficient ancient cultures that already displayed signs of universalization. The paper also defines the nature of the “break” of the Ancient Era, which led to the disappearance of the Chernyakhiv culture around the middle of the first millennium CE. Petrov believed that this rupture was caused by the deep crisis of the Roman Empire in the second half of the IVth century and the collapse of the old-world system of connections, based on Rome’s supremacy among other peoples. The Hunnic invasion merely intensified the pre-existing crisis. The focus of the research is directed toward highlighting the connection between Ukrainian culture and European civilization as an equal and self-sufficient component whose roots reach back to Antiquity. Petrov’s concept, emphasizing discreteness, ruptures, and autonomous devel-opment, is presented within the context of XXth–early XXIth century historical and archaeo-logical thought as a novel and still scientifically relevant theory, confirmed by the works of modern researchers.